Investigation on the Sodium cooled fast reactor (SFR) - Lim, Teck Meng (2015)
This report documents Final Year Project No. A1076-141, Investigation on the sodium cooled fast reactor. Sodium cooled fast reactor (SFR) has been selected and categorised as the Generation IV reactor. It is intended for use in nuclear power plants to produce nuclear power from nuclear fuel, and many countries are using it as their nuclear reactor. Sodium is the main chemical element in SFR, and the SFR comprises three types of properties: physical, chemical and neutronic. These three properties are discussed to understand more on the design of SFR using sodium. In addition, the fundamental of atoms, fuel design and its main components of the overall system will be also discussed. For example, fuel element, type of concept and the heat transport circuit. It also includes the safety on the sodium and other parts of the SFR.